Fichte's Philosophy of Religion and the Gospel of John - Andrey Sudakov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2019)
After the “atheism dispute”, Fichte formulated, in an esoteric and essayistic form, the philosophy of life in God that would accord with the doctrine of the “true Christianity”, the only teacher of which, in Fichte’s opinion, was Apostle John. This article reconstructs the philosophical theology and Christology of the Way towards the Blessed Life and discusses Fichte’s arguments in favour of the specifi c signifi cance of the Gospel of John for contemplative philosophy and religious life, as well as a range of key problems of his philosophy of religion which Fichte sets out following John’s theology, i.e. the problem of the relationship of the metaphysical and historical in the text of the Gospel and in the content of the Christian doctrine; Fichte’s philosophical Christology; his specifi c iterpretation of the communion and the question about the “essence” of Christian life. The antithesis of metaphysical and historical appears to be their inseparable unity, because being separated, the metaphysical content of religion remains a mere “doctrine of religion” and, hence, a false conscience. Philosophical idea of Christ as the only embodiment of the blissful religious life in history that came to be the immediate conscience, serves as a speculative correction of the almost blasphemous appeals “to fully repeat it in one’s own personality”. The metaphor of transsubstantiation, transferred from the context of the religious sacrament to the context of the integrity of the “believing life”, because of its invariable emphasis on the practical activity in the spirit of one’s own belief, can become the source for the new philosophy of Christian life. On the whole, it becomes clear that in his interpretation of the Gospel of John, Fischte has a speculative “trnscription”, if not theological exegesis; the spirit and language of Fichte’s speculation do not allow this transcription to follow the way of the rational and secular decomposition of the content of the Evangelical message, which was naturally taking place in the philosophy of Enlightenment.